The 28S rRNA RT-qPCR assay for host depletion evaluation to enhance avian virus detection in Illumina and Nanopore sequencing - Goraichuk, Iryna V.; Harden, Mark; Spackman, Erica; Suarez, David L. (Frontiers in Microbiology, 2024)
Abundant host and bacterial sequences can obscure the detection of less prevalent viruses in untargeted next-generation sequencing (NGS). Efficient removal of these non-targeted sequences is vital for accurate viral detection. This study presents a novel 28S ribosomal RNA (rRNA) RT-qPCR assay designed to assess the efficiency of avian rRNA depletion before conducting costly NGS for the detection of avian RNA viruses. The comprehensive evaluation of this 28S-test focuses on substituting DNase I with alternative DNases in our established depletion protocols and finetuning essential parameters for reliable host rRNA depletion. To validate the effectiveness of the 28S-test, we compared its performance with NGS results obtained from both Illumina and Nanopore sequencing platforms. This evaluation utilized swab samples from chickens infected with highly pathogenic avian influenza virus, subjected to established and modified depletion protocols. Both methods significantly reduced host rRNA levels, but using the alternative DNase had superior performance. Additionally, utilizing the 28S-test, we explored cost-and time-effective strategies, such as reduced probe concentrations and other alternative DNase usage, assessed the impact of filtration pre-treatment, and evaluated various experimental parameters to further optimize the depletion protocol. Our findings underscore the value of the 28S-test in optimizing depletion methods for advancing improvements in avian disease research through NGS.